PEMBERDAYAAN MASYARAKAT TERDAMPAK COVID-19 MELALUI USAHA BUDIDAYA LELE PADA LAHAN PERKEBUNAN DI DESA GALUNGAN,BULELENG - Pebriani, D.A.A.; Negara, I.K.W.; Wijayanti, N.P.P.; Suryaningtyas, E.W.; Pratiwi, M.A. (Buletin Udayana Mengabdi; Vol 21 No 2 (2022): Buletin Udayana Mengabdi, 2022)
The existence of COVID-19 has had a very large impact on economic conditions throughout the world, one of the business fields that has been greatly affected by this pandemic is the business sector of tourism activities. Until now, people in the Province of Bali have relied heavily on businesses in the tourism sector, which directly experienced a tremendous impact due to economic shocks, so that this condition resulted in several people who depended on tourism for their livelihoods choosing to return to their home villages due to layoffs or losses due to business. which is not profitable. Buleleng Regency has an area of ??1,365.88 km² or 24.25% of the island of Bali, so it has the largest land and water area in the Province of Bali. There are many activities that can be used as a source of livelihood during this pandemic, one of which is fish farming. Catfish farming is one of the activities of choice in the midst of this pandemic because it is practical and productive. Practical because it is easy to apply and can even use plantation land as a location for cultivation and produce because the harvest can not only be consumed by cultivators but can also be sold which of course provides economic value. The purpose of this service activity is to provide solutions to problems of economic opportunity for communities affected by COVID-19 and the use of plantation land for catfish cultivation with the application of round tarpaulin ponds, so as not to interfere with the main commodities of the plantation land. Tarpaulin ponds are one solution for the development of catfish cultivation on plantation land so that the land, in addition to getting production from its main commodity, also gets additional results from catfish production. The service activity took place on August 21, 2021 in Galungan Village by involving the community starting from the preparation, implementation, and evaluation stages. The community was very enthusiastic about following the presentation from Mr. Dr. Pande Gde Sasmita Julyantoro, S.Si., M.Si and Mr. Nyoman Agus Sudarta, S.Pi, judging by the feedback given by the community in the form of questions related to catfish farming using tarpaulin ponds.   Keywords: aquaculture method, catfish (Clarias sp.), community empowerment, Galungan Village.